2018
DOI: 10.1186/s13568-018-0655-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of black queen cell virus and Kashmir bee virus in honey

Abstract: Considering the intensive trading nowadays, the honey from the local market was tested for the presence of the six most common bee viruses. To prove the suitability of honey as a sample for the bee viruses detection, the set of different sample types taken directly from the hives we comparatively tested. The study included 30 samples of domestic and 5 samples of imported honey. Additionally, we tested 40 sets of samples including live bees, dead bees, and the honey taken from four apiaries for the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the phylogenetic analysis of partial capsid protein gene (Fig.1), the sequences of this study (BR-BQCV) showed greater similarity with Asian sequences and sequences from the United States (USA), Germany and Peru. The sequences from Belgium, Kyrgyzstan and Georgia are grouped into a distinct cluster, suggesting that geographic origins of sequences can be decisive for their genetic divergence (Roberts et al 2017, Milićević et al 2018, Prodělalová et al 2019. The sequence from Brazil D6 (EU292211), collected in 2007 in the Southeast region, was grouped in a different cluster when compared with the samples from this study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the phylogenetic analysis of partial capsid protein gene (Fig.1), the sequences of this study (BR-BQCV) showed greater similarity with Asian sequences and sequences from the United States (USA), Germany and Peru. The sequences from Belgium, Kyrgyzstan and Georgia are grouped into a distinct cluster, suggesting that geographic origins of sequences can be decisive for their genetic divergence (Roberts et al 2017, Milićević et al 2018, Prodělalová et al 2019. The sequence from Brazil D6 (EU292211), collected in 2007 in the Southeast region, was grouped in a different cluster when compared with the samples from this study.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported the active replication of virus in drones and the transmission through semen (Alger et al 2019, Prodělalová et al 2019. BQCV has already been detected in flowers collected from the apiaries (Alger et al 2019), and in samples of honey (Milićević et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Robbing of honey bee colonies by bumble bees (Genersch et al, 2006) and wasps has also been documented, but is more individual rather than systematic and usually toward the end of summer when both wasp and bumble bee colonies are in natural decline. Viruses can certainly be detected in honey (Milićević et al, 2018), so that robbing honey does expose robbing bees and wasps to potential infection (Genersch et al, 2006), but direct evidence for virus transmission through honey is so far absent, for honey bees or bumble bees.…”
Section: Inter-species Virus Transmissionmentioning
confidence: 99%
“…A large number of methods and techniques have been developed for the identification of various honey bee pathogens [9][10][11]. One of the most widely used methods for the detection of a particular pathogen is the amplification of coding and/or noncoding DNA regions, followed by a sequence analysis of the amplified DNA fragment [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most often forager bees and, less frequently, house bees, drones, or brood are used as a source of biological material for the identification of a particular pathogen. Alternatively, a large number of honey bee pathogens may be detected in honey bee products-usually, honey, propolis, and bee wax [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%